Differential reaction of sweet pepper to infection with the crinivirus tomato chlorosis virus probably depends on the viral variant - Vicentin, Eduardo [UNESP]; Mituti, Tatiana; Nogueira, Angélica Maria [UNESP]; Moura, Mônika Fecury [UNESP]; Bello, Vinicius Henrique [UNESP]; Ribeiro Júnior, Marcos Roberto [UNESP]; Wintermantel, William M.; Olivé, Elvira Fiallo; Navas-Castillo, Jesús; Krause-Sakate, Renate [UNESP]; Rezende, Jorge Alberto Marques (Wiley, 2022)
The tomato chlorosis virus (ToCV), transmitted by whitefly species of the genera Bemisia and Trialeurodes in a semipersistent manner, causes significant losses in solanaceous crops including tomato (Solanum lycopersicum) and sweet pepper (Capsicum annuum). Worldwide reports of natural and experimental infection of sweet pepper plants with ToCV are contradictory, raising the question of whether the critical factor determining infection is related to the susceptibility of sweet pepper cultivars or the genetics of virus isolates. In this work, ToCV isolates obtained from different hosts and geographical origins were biologically and molecularly analysed, transmitted by B. tabaci MEAM1 and MED, and the reaction of different sweet pepper cultivars was evaluated under different environmental conditions. Brazilian ToCV isolates from tomato, potato (S. tuberosum), S. americanum, and Physalis angulata did not infect plants of five sweet pepper cultivars when transmitted by B. tabaci MEAM1. Temperatures did not affect the sweet pepper susceptibility to tomato-ToCV isolates from São Paulo, Brazil, and Florida, USA. However, sweet pepper-ToCV isolates from Spain and São Paulo, Brazil, were transmitted efficiently to sweet pepper plants by B. tabaci MEAM1 and MED. Although the results indicated that ToCV isolates from naturally infected sweet pepper plants seem to be better adapted to plants of C. annuum, phylogenetic analyses based on the complete nucleotide sequences of RNA1 and RNA2 as well as the p22 gene did not reveal significant nucleotide differences among them. Additional studies are needed to identify intrinsic characteristics of ToCV isolates that favour infection of sweet pepper plants.
Keywords: Bemisia tabaci; interaction; plant susceptibility; virus; whitefly